Differences in the Awareness and Knowledge of Radiological and Nuclear Events Among Medical Workers in Japan - Kanae Ochiai; Tomo Oka; Nagisa Kato; Yuji Kondo; Yasuhiro Otomo; Raymond E. Swienton (Frontiers Media S.A., 2022)
BackgroundPrevious research revealed a lack of comfort and knowledge regarding nuclear and radiological events among medical staff. We investigated the awareness and knowledge of radiological and nuclear events among the Japanese medical staff by comparing differences by occupation (doctors, nurses, and other medical specialists).MethodsWe conducted a cross-sectional questionnaire survey among trainees undergoing Japanese disaster medical training courses between July 2014 and February 2016. The differences by occupation were evaluated for all questions on awareness and knowledge concerning disasters or radiological and nuclear events and demographics.ResultsAmong the occupations, there were significant differences in the willingness to work onsite based on the types of disaster, familiarity with the national disaster medical response system, the accuracy rate of some knowledge about medical practice and the risk, and demographic characteristics such as practical experience and educational degree. The accuracy rates of responses to some questions on knowledge were very low in all occupations.ConclusionThere were significant differences in awareness and knowledge of radiological and nuclear events by occupation. We believe that the results can be used to develop and modify the content of training courses on radiological and nuclear events to make such courses beneficial for each healthcare worker.